Distribution, aggregate demand and productivity growth - theory and empirical results for six OECD countries based on a Post-Kaleckian model - Eckhard Hein; Artur Tarassow (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
Empirical research based on the Bhaduri/Marglin-variant of the Kaleckian model has recently shown that aggregate demand in many medium-sized and large open economies tends to be wage-led in the medium to long run, even in a period of increasing globalisation. In this paper we extend this type of analysis and integrate the effects on productivity growth, theoretically and empirically. Productivity growth is introduced into the theoretical model making use of the Verdoorn effect or of Kaldor's technical progress function and hence of a positive relationship between GDP or capital stock growth and productivity growth. Further on, a costpush or Marx/Hicks-effect and hence a positive impact of real wage growth or the wage share on productivity growth is taken into account. In the empirical part we estimate productivity growth equations for six countries introducing these two effects. Finally, economic policy conclusions are drawn.
urn:nbn:de:101:1-2008110498
Keywords: E12; E21; E22; E25; O41; 330; Demand-led growth; endogenous technical change; wage-led and profit-led demand regimes; productivity regime; Verteilungstheorie; Produktivität; Endogener technischer Fortschritt; Theorie; Schätzung; Österreich; Frankreich; Deutschland; Niederlande; USA; Großbritannien